Phytodiversity and conservation of Nithypooja Kona Sacred Grove of Nallamala Hill Range, Eastern Ghats, Andhra Pradesh - Basha, SKM; Paul, M John; Reddy, P Siva Kumar (International Journal of Environment, 2015)
Sacred groves are climax forests and are the only representatives of natural or near-natural vegetation. These are dedicated to deities or ancestral spirits worshipped by local tribes along with surrounding plants and trees. These are ecosystems by themselves and perform all the ecological functions. Phytodiversity constitute a large segment of the flora which provides raw materials for use by numerous Pharmaceutical industries. The present study will be useful for researchers in the field of Ethan botany, Ethnomedicine, Taxonomy, and Pharmacology for further studies. Nithyapoojakona Sacred grove is one of the important sacred groves in Kadapa district. The present paper deals with the phyto-diversity of the above grove used by local tribes. This paper deals with the 181 species of probable medicinal potential belonging to 138 genera and 71 families. Significant flora are Cycas beddomei, Pterocarpus santalinus, Drosera burmaptonni, Orabanche cernua, Neptunia oleracea, Hugonia mystax, Caralluma adsendens , Gloriosa superba, Limnophila spp, Centella sasiatica etc. Word famous Red sanders population of the study area is being destroyed unethically and it is to be protected. DOI: http://dx.doi.org/10.3126/ije.v4i2.12648 International Journal of Environment Vol.4(2) 2015: 271-288